Online Social Capital as a Catalyst for Female Entrepreneurship - Rahmatika, Rizka Astari; Purnomo, Lorio; Wibawa, Rafki Chandra; Pratiwi, Chairani Putri (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
Social capital is an essential factor which supports the progression of entrepreneurship, and many recent studies have examined its positive relations to individual empowerment. Although many studies focus on social capital, research on online social capital in the context of vulnerable groups, such as women, still needs further examination. This paper aims to examine the role of online social capital in the development of female entrepreneurship by examining various constructs it may affect. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, we conducted a systematic review to map existing literature from 2018 until 2023. The finding confirms that online social capital, bonding, bridging, or both, positively influence several constructs, such as social connections, emotional support, entrepreneurial perception and opportunity process, self-efficacy, and empowerment.